Integrated catalysis opens new arylation pathways via regiodivergent enzymatic C–H activation - Jonathan Latham (Nature Portfolio, 2016)
Biocatalysis and metal catalysis often provide complimentary reactivities and selectivities. Here, the authors exploit the regioselectivity of an enzymatic C–H activation followed by palladium catalysed carbon-carbon bond formation in one pot, with membrane compartmentalization used to isolate the two chemistries.